Reducing unwarranted antibiotic use for pediatric acute otitis media: the influence of physicians' explanation and instruction on parent compliance with 'watchful waiting'. Issue 3 (27th May 2017) - MacGeorge, Erina L.; Caldes, Emily P.; Smith, Rachel A.; Hackman, Nicole M.; San Jose, Alyssa
ABSTRACT: 'Watchful waiting' (WW) involves prescribing antibiotics but advising against use unless the illness fails to improve in a set time. For childhood ear infections, WW can reduce unnecessary antibiotic use, but parents do not necessarily comply with WW advice. This study examines how physician explanation and instruction is related to parental compliance. A national sample of parents ( N = 134) who received WW advice reported what they remembered physicians saying. These responses were coded for explanatory and instructional elements indicated by relevant clinical guidelines. Parents also reported whether they complied with the WW advice or administered the antibiotic immediately. Parental compliance was predicted by explanation of the nature of ear infections, instruction on monitoring, and instruction on managing pain. Few parents reported any explanation about antibiotics' adverse effects. Findings suggest physicians can improve parent compliance with WW by improving the quality of the explanation and instruction they provide.